Literary Translingualism in the United Arab Emirates: Anglophone Emirati prose and poetry - Doris Hambuch; Moza Al Tenaijy; Aisha Khamis Aldarmaki; Ali Nawab Alblooshi (Cogent Arts & Humanities)
This study investigates the motivations of Emirati creative writers to choose the global language, English, rather than the UAE’s official language, Arabic, for their literary texts. Much scholarship has been dedicated to the role of English in the Gulf region, but hardly any of this research focusses on the arts. Drawing upon studies of anglophone literature from other countries where English is not an official language, content analysis, and a case study, this article identifies the reach for international audiences as the main motivation, followed by personal language command. Literary influence and genre selection are minor reasons causing Emirati writers to published in English. Situating the small but steadily growing translingual, or exophonic Emirati canon within the short local literary history as well as within a global anglophone context, the article also demonstrates that innovative uses of language may occur. Regional efforts to promote local authors along with changing publishing conditions will likely lead to an expansion of the studied canon in the near future.